2004
DOI: 10.17796/jcpd.28.1.buq243j955771h48
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of the palatal plate therapy for the orofacial regulation in children with Down syndrome

Abstract: The objective of this study was to evaluate long term effects of orofacial regulation therapy with modified Castillo-Morales palatal plate on 68 Down children that attended our Unit from 1992 to 2001. Corrections obtained with palatal plate therapy were evaluated according to the following parameters: spontaneous lingual protrusion based on three level scale, position "open mouth", labial hypotonia and sialorrhea. The results showed distinct improvement in nearly all of the parameters compared to initial condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 2 publications
0
31
0
5
Order By: Relevance
“…Only the child who never used either of the two plates was excluded. Previous studies have not accounted explicitly for compliance, but the number of dropouts reported indicate that compliance could have been of the same magnitude as in this study 5,6,8,23 .…”
Section: Discussionmentioning
confidence: 57%
“…Only the child who never used either of the two plates was excluded. Previous studies have not accounted explicitly for compliance, but the number of dropouts reported indicate that compliance could have been of the same magnitude as in this study 5,6,8,23 .…”
Section: Discussionmentioning
confidence: 57%
“…Zur Förde-rung der Koordination und Funktion der orofazialen Muskulatur hat sich -ähnlich wie bei Kindern mit Lippen-Kiefer-Gaumen-Spalten oder Trisomie 21 -das sog. Castillo-Morales-Konzept bewährt [14,22]. Durch Schlucken wird die Tubenbelüftung gefördert und die Häufigkeit von Schallleitungsstörungen mit dieser Therapiemethode vermindert [5].…”
Section: Therapieunclassified
“…2,14,19,20 Muscle hypotonia associated with a reduced volume of the oral cavity and characterized by a deep, atresic palate may lead to a tendency toward habitually projecting the tongue against the teeth or outside the mouth. 5,18,21 Abnormal function and the position of the tongue can affect tooth eruption causing anterior open bite, tooth alignment, and the arch shape. 12,22 However, these variables were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 99%